The Effect of Environmental Management Accounting (EMA) on Financial Performance and Working Capital Management (WCM) as Mediating Variables - Prasetya, Syarief Gerald; Safitri, Julia (Jurnal Manajemen, 2023)
Sustainable accounting is a concern where demands on financial information become wider. The research aims to analyze the effect of EMA on the company’s financial performance and working capital management (WCM) as a mediator. The data was obtained through a questionnaire survey of seventy eight respondents from textile manufacturing companies in Bogor Regency. The path analysis model is tested using Smart PLS. The results of the study found that EMA has a direct significant effect on financial performance and the role of working capital management as a mediator contributes to the indirect effect of EMA on financial performance. EMA information is critical in providing information that increases managers’